Pengembangan model pembelajaran Teams-Games-Tournament (TGT) dalam pembelajaran kosakata Bahasa Jerman (Wortschatz) di SMA Kota Makassar - Misnawaty Usman; Ambo Dalle (Seminar Nasional LP2M UNM, 2019)
The purpose of this study was to obtain information about the effectiveness of German vocabulary learning (Wortschatz) based on the Teams-Games-Tournaments (TGT) learning model. The subjects involved in this study were teachers and class XI students of Makassar 11 Public High School. The research data was collected through a device implementation sheet, questionnaire and test. The quality of learning devices is viewed from three aspects, namely; validity, practicality, and effectiveness. The results showed that the German vocabulary learning device (wortshatz) based on the Teams-Games-Tournaments (TGT) learning model was valid, practical, and effective. Test the effectiveness of learning devices using the t-test formula and the results of data analysis show that th (10.128)> tt (2.002) with the level of alpha (α) 0.05. The results showed that learning devices based on the Teams-Games-Tournaments (TGT) learning model were effective in learning German vocabulary.